2021
DOI: 10.9734/jpri/2021/v33i41b32366
|View full text |Cite
|
Sign up to set email alerts
|

The Phytochemical and Pharmacological Properties of Persicaria odorata: A Review

Abstract: World Health Organization (WHO) reported that 88% of its member or 61 countries acknowledge the use of traditional and complementary medicines. Persicaria odorata is being used as traditional herbs to treat fever, nausea and promoting hair growth. Besides, it is used as an anti-inflammatory agent in Vietnam to relieve swelling and treat wounds, sores, and ulcers. This review aims to evaluate the phytochemical and pharmacological status of P. odorata. P. odorata is a plant with a high content of phenols and fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Therefore, the phytochemical components of each extract might differ. In 2021, Azmi et al reported that different phytochemical constituents were present in various parts of P. odoratum ( Azmi et al, 2021 ). Moreover, the different extraction methods used by the studies produced diverse chemical profiles ( Chansiw et al, 2019 ; Nguyen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the phytochemical components of each extract might differ. In 2021, Azmi et al reported that different phytochemical constituents were present in various parts of P. odoratum ( Azmi et al, 2021 ). Moreover, the different extraction methods used by the studies produced diverse chemical profiles ( Chansiw et al, 2019 ; Nguyen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%